Assessment of Tanshinone IIA Derivatives for Cardioprotection in Myocardial Ischemic Injury - Wu, Zhiwu; Xu, Ying; Guo, Ximing; Zhang, Zhilan; Wang, Jinxin; Tang, Yiqun (Planta Medica, 2025)
Tanshinone ⅡA (TSA), a component of traditional Chinese medicine, effectively protects against myocardial injury. However, its clinical application is limited by poor water solubility and a short half-life. In this study, we report on four TSA derivatives designed and synthesized by our research group. The protective activity against hypoxia-reoxygenation injury in cells was evaluated, and derivative Ⅰ-3 was selected for in vivo experiments to verify its myocardial protective activity in rats with myocardial infarction. The results demonstrated that these four compounds could protect neonatal rat cardiomyocytes from hypoxia-reoxygenation injury. Among the derivatives, Ⅰ-3 showing superior protective effects, we found that Ⅰ-3 has enhanced metabolic stability and an extended half-life. Ⅰ-3 exhibited superior biological activity, effectively reducing the heart infarction area, alleviating myocardial hypertrophy, and enhancing cardiac pumping function. Ⅰ-3 reported in the present work represents a novel and effective derivative of TSA, showing great potential for the treatment of myocardial ischemia (MI).
Keywords: Salvia miltiorrhiza; Lamiaceae; Tanshinone ⅡA; derivatives; myocardial ischemia; coronary artery ligation; cardiomyocytes; hemodynamic